2020
DOI: 10.48550/arxiv.2005.04354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exact Asymptotics for Learning Tree-Structured Graphical Models with Side Information: Noiseless and Noisy Samples

Abstract: Given side information that an Ising tree-structured graphical model is homogeneous and has no external field, we derive the exact asymptotics of learning its structure from independently drawn samples. Our results, which leverage the use of probabilistic tools from the theory of strong large deviations, refine the large deviation (error exponents) results of Tan, Anandkumar, Tong, and Willsky [IEEE Trans. on Inform. Th., 57(3):1714-1735 and strictly improve those of Bresler and Karzand [Ann. Statist., 2020]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Chow and Wagner [CW73] showed that the Chow-Liu algorithm consistently recovers structure, meaning that if the samples are generated by a T -structured distribution for a tree T , then it recovers T with probability approaching 1 as the number of samples tends to infinity. More recent works [TATW11,TTZ20] have used large-deviation theory to study the error exponent K P of T -structured distributions P , where:…”
Section: Introductionmentioning
confidence: 99%
“…Chow and Wagner [CW73] showed that the Chow-Liu algorithm consistently recovers structure, meaning that if the samples are generated by a T -structured distribution for a tree T , then it recovers T with probability approaching 1 as the number of samples tends to infinity. More recent works [TATW11,TTZ20] have used large-deviation theory to study the error exponent K P of T -structured distributions P , where:…”
Section: Introductionmentioning
confidence: 99%